The Hunchback of Notre Dame - Hugo, Victor, 1802-1885; Blaisdell, Robert; Kliros, Thea; Hugo, Victor, 1802-1885. (New York : Dover Publications, 1995)
A retelling of the tale, set in medieval Paris, of Quasimodo, the hunchbacked bellringer of Notre Dame Cathedral, and his struggles to save the beautiful gypsy dancer Esmaralda from being unjustly executed.
Keywords: Notre-Dame de Paris (Cathedral) -- Fiction; Physically handicapped -- Fiction; France -- History -- Medieval period, 987-1515 -- Juvenile fiction; France -- History -- Medieval period, 987-1515 -- Fiction; Paris (France) -- Fiction